Embedding research into health services in Latin America and the Caribbean: experiences and challenges of the Technical Support Center - Víctor Becerril-Montekio; Pilar Torres-Pereda; Luis Alberto García-Bello; Jacqueline Alcalde-Rabanal (Pan American Health Organization, 2021)
This article describes the main models for embedding research and the successful experiences and challenges faced in joint work by researchers and decisionmakers who participated in the Embedding Research for the Sustainable Development Goals (ER-SDG) initiative, and the experience of the Technical Support Center. In June 2018, funding was granted to 13 pre-selected research projects from 11 middle- and low-income countries in Latin America and the Caribbean (Argentina, Bolivia, Brazil, Colombia, Dominican Republic, Ecuador, Guatemala, Guyana, Haiti, Paraguay, and Peru). The projects focused on the system-, policy-, or programlevel changes required to improve health and build on the joint work of researchers and decisionmakers, with a view to bringing together evidence production and decision-making in health systems and services. The Technical Support Center supported and guided the production of quality results useful for decision-making. This experience confirmed the value of initiatives such as ER-SDG in consolidating bridges between research on the implementation of health policies, programs, and systems, and the officials responsible for operating health-related programs, services, and interventions. It highlighted the importance of both respecting and taking advantage of each context-and the specific arrangements and patterns in the relationships between researchers and decisionmakers-through incentives for embedded research.